Tax Incidence in the Presence of Tax Evasion - Philipp Doerrenberg; Denvil Duncan (Institute for the Study of Labor (IZA), 2014)
This paper studies the effect of tax evasion on the economic incidence of sales taxes. We design a laboratory experiment in which buyers and sellers trade a fictitious good in double auction markets. A per-unit tax is imposed on sellers, and sellers in the treatment group are provided the opportunity to evade the tax whereas sellers in the control group are not. We find that the market equilibrium price in the treatment group is economically and statistically lower than in the control group. This result is consistent with a theoretical model in which access to evasion opportunities reduces the effective tax rate and therefore dampens real behavioral responses. Our findings suggest that the benefits of tax evasion are not limited to the side of the market with access to evasion but are partly shifted to the non-evading side of the market. We discuss the implications of our findings for the distributional and welfare effects of taxes.
Keywords: H21; H22; H26; H3; D44; 330; tax evasion; tax incidence; double auction